Fish scaling machines / Adam Habri and Haszeme Abu Kasim - Habri, Adam; Abu Kasim, Haszeme (School of Mechanical Engineering, 2023)
Fish is an important food source for humans, but the scales must be removed before cooking. Currently, there is no cost-effective and efficient machine available for removing fish scales, so people must use their hands to clean the fish. This project aims to design and create an affordable machine that can effectively remove fish scales. The methodology for this project involves selecting the best design from three proposed sketches and conducting engineering calculations based on specific dimensions. The fish scaling machine will be fabricated and analyzed, with costs determined and fabrication steps specified. The goal is to develop a machine that can clean fish scales efficiently, replacing the need for manual labor.